2004
DOI: 10.1128/mcb.24.4.1505-1515.2004
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase B/Akt Acts via Glycogen Synthase Kinase 3 To Regulate Recycling of αvβ3 and α5β1 Integrins

Abstract: Protein kinase B (PKB)/Akt is known to promote cell migration, and this may contribute to the enhanced invasiveness of malignant cells. To elucidate potential mechanisms by which PKB/Akt promotes the migration phenotype, we have investigated its role in the endosomal transport and recycling of integrins. Whereas the internalization of ␣v␤3 and ␣5␤1 integrins and their transport to the recycling compartment were independent of PKB/Akt, the return of these integrins (but not internalized transferrin) to the plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
137
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(146 citation statements)
references
References 55 publications
8
137
1
Order By: Relevance
“…4D). Glycogen synthase kinase 3␤ is a target of PKB␣ known to phosphorylate kinesin light chain and, thus, to negatively regulate kinesin-based motility and integrin recycling (37,38). We observed hyperphosphorylated kinesin light chain 2 in ANGPTL4 Ϫ/Ϫ wounds, which suggested that integrin recycling may be impaired in ANGPTL4-deficient keratinocytes (Fig.…”
Section: Angptl4 Interacts With Matrix Proteins and Delaysmentioning
confidence: 64%
“…4D). Glycogen synthase kinase 3␤ is a target of PKB␣ known to phosphorylate kinesin light chain and, thus, to negatively regulate kinesin-based motility and integrin recycling (37,38). We observed hyperphosphorylated kinesin light chain 2 in ANGPTL4 Ϫ/Ϫ wounds, which suggested that integrin recycling may be impaired in ANGPTL4-deficient keratinocytes (Fig.…”
Section: Angptl4 Interacts With Matrix Proteins and Delaysmentioning
confidence: 64%
“…Dominant negative construct of IB␣ (pCMV-IB␣M) was purchased from Clontech (Mountain View, CA). Human MMP-13 promoter construct and plasmid expression vector containing siRNA targeting Akt (Mu6pro-Akt1/2) and control siRNA plasmid construct (Mu6pro) were previously described (27,29,30). The p3xNFBLuc plasmid construct, containing three copies of tandemly repeated NFB response element sequences (5Ј-TTG-GGCACTCCCTG-3Ј) of MMP-13 promoter region was achieved by placing the NFB response elements of MMP-13 promoter region upstream of an SV40 promoter at the SacI site of the pGL3-promoter vector, which contains a luciferase reporter gene system (Promega) as described previously (31).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, our recent study showed that kallikrein gene delivery protects against cerebral ischemia injury and apoptosis along with activation of Akt signaling (6). Activation of Akt triggers downstream signaling pathways such as GSK-3 phosphorylation in a variety of cell lines (7). GSK activity is inactivated by Akt-induced phosphorylation at serine 21 (␣ isoform) and serine 9 (␤ isoform), leading to inhibition of apoptosis in insulin-mediated signal transduction (8,9).…”
mentioning
confidence: 99%